Game Virtual Tour Pengenalan Sistem Tata Surya Berbasis VR Google Cardboard dan Voice Command - Muh Ulil Alkhaq; Siti Asmiatun (Sekawan Institut, 2026)
The solar system is an essential topic in elementary school science education, playing a role in developing students' critical thinking skills and scientific understanding. However, conventional teaching methods often make students passive recipients of information, discouraging interaction and independent exploration. This can decrease interest and engagement in learning. Therefore, a more interactive and engaging approach is necessary to teach students about the solar system ef-fectively. This game uses VR technology and voice commands to provide an immersive experience exploring the solar system. Players can interact with objects in the solar system. It also features voice control, which allows students to interact with objects in the solar system and access addi-tional information. The average score on the questionnaire survey of the application was 86.30%. Integrating VR and voice commands has proven effective in increasing students' interest in learn-ing and facilitating navigation in immersive learning environments.